ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI JAGUNG MANIS DI DESA SOULOVE KECAMATAN SIGI BIROMARU KABUPATEN - Nurlaela, Nurlaela; Antara, Made; kalaba, Yulianti (AGROTEKBIS, 2018)
The agricultural sector is the primary sector encouraging and driving the national economy. The agricultural sector also has functions of providing food for the society and also contributing foreign exchange as well as providers of employment and raw materials for the industrial sectors. Indonesian people who live in rural areas make agriculture as the main livelihood and food crops are the superior commodity in Indonesia. This research was conducted in Soulove village, SigiBiromarusub district, Sigiregency. This research used 30 respondents selected from 90 farmers using a simple random sampling method.Data analysis used a Cobb-Douglas production function and price efficiency which was NPM = Pxi. The purposes of this research were to determine the production input influence on sweet corn production and to determine the level of efficiency of input production used on sweet corn farming system in Soulove Village, Sigi Biromaru District, Sigi Regency. The analysis results of the research shows that land area size, seeds, fertilizers, pesticides and labors simultaneouslyaffected the production of sweet corn significantly, at Î± level of 1%. The results of efficiency analysis showed that the use of land area (x1) by the sweet corn farmers had not been efficient while the use of seed (x2), fertilizer (x3), pesticide (x4) and labor (x5) by sweet corn farmers was inefficient.Â Keywords: Analysis Efficiency, Cobb-Douglas, Sigi Regency, Sweet Corn.